2023
DOI: 10.1200/jco.22.02208
|View full text |Cite
|
Sign up to set email alerts
|

The Childhood Cancer Data Initiative: Using the Power of Data to Learn From and Improve Outcomes for Every Child and Young Adult With Pediatric Cancer

Joseph A. Flores-Toro,
Subhashini Jagu,
Gregory T. Armstrong
et al.

Abstract: Data-driven basic, translational, and clinical research has resulted in improved outcomes for children, adolescents, and young adults (AYAs) with pediatric cancers. However, challenges in sharing data between institutions, particularly in research, prevent addressing substantial unmet needs in children and AYA patients diagnosed with certain pediatric cancers. Systematically collecting and sharing data from every child and AYA can enable greater understanding of pediatric cancers, improve survivorship, and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Because the fusionstratified analysis was limited by sample size, a larger sample of patients who had fusion-positive RMS is needed to validate these results. 28 In the present study, none of the patients with fusionpositive RMS harbored a CPV. 13 Because survival was comparable to patients with fusion-positive RMS, CPV status among patients with fusion-negative RMS might represent an important prognostic factor for this group of patients.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 41%
See 1 more Smart Citation
“…Because the fusionstratified analysis was limited by sample size, a larger sample of patients who had fusion-positive RMS is needed to validate these results. 28 In the present study, none of the patients with fusionpositive RMS harbored a CPV. 13 Because survival was comparable to patients with fusion-positive RMS, CPV status among patients with fusion-negative RMS might represent an important prognostic factor for this group of patients.…”
Section: Jama Network Open | Pediatricsmentioning
confidence: 41%
“…We also found that the outcome among patients who had fusion-negative RMS with a CPV was not significantly different than patients who had fusion-positive RMS; the outcome was worse compared with patients with fusion-positive RMS, although this association was not statistically significant. Because the fusion-stratified analysis was limited by sample size, a larger sample of patients who had fusion-positive RMS is needed to validate these results . In the present study, none of the patients with fusion-positive RMS harbored a CPV .…”
Section: Discussionmentioning
confidence: 74%
“…Project:EveryChild also provided an efficient platform to launch the Childhood Cancer Data Initiative (CCDI) Molecular Characterization Initiative (MCI) in March 2022 7 . To address the unequal access to molecular testing at diagnosis, MCI is open to children, adolescents, and young adults with newly diagnosed central nervous system tumors, soft tissue sarcomas, and selected rare tumors.…”
Section: Year Of Pediatric Labeling Agent Indication Cog Studymentioning
confidence: 99%
“…Currently, MCI is open for enrollment of children and adolescent and young adult (AYAs) with newly diagnosed central nervous system tumors, soft tissue sarcomas, or rare tumors, who are undergoing treatment at a COG member institution and enrolled on COG's Project EveryChild. 1 Enrollment will soon extend to patients with newly diagnosed high-risk neuroblastoma, followed by Ewing sarcoma, to coincide with forthcoming COG clinical trials.…”
Section: Expanding Access To Molecular Characterizationmentioning
confidence: 99%